Spatio-Temporal Pattern of Carbon Emission and Optimization Strategy of Emission Reduction Path in Beijing From the Perspective of Green Finance - Wang, Fuxing (Asia Pacific Economic and Management Review, 2025)
Beijing, as the capital of China and the pioneer of low-carbon transition, faces the dual challenges of deep emission reduction and economic development. From the perspective of green finance, this study combines spatio-temporal pattern analysis and coupled coordination model to systematically explore the characteristics of Beijing’s carbon emissions and the optimization strategy of emission reduction path from 2000 to 2023. The study finds that: Beijing’s carbon emissions show the spatial and temporal differentiation characteristics of "high concentration in the core area and low diffusion in the remote suburban areas", the carbon center is stable in Changping District for a long time, but the emerging urban areas, such as Chaoyang and Haidian Districts, have outstanding carbon emission intensity; the coupling and coordination degree of green finance and carbon emissions shows a leaping trend of "primary to intermediate to good coordination"; and the coupling and coordination degree of green finance and carbon emissions shows a leaping trend of "primary to intermediate to good coordination". The degree of coordination of green finance and carbon emission coupling shows a trend of "primary→intermediate→good→coordinated", but there is a significant regional differentiation, with insufficient transformation momentum in the core urban areas and long-term lagging in the peri-urban industrial areas. By constructing a four-dimensional path framework of "scale effect - technology effect - structure effect - spatial effect", differentiated emission reduction strategies are proposed.